(untitled) (NTU journal for Administrative and Human Sciences (JAHS), 2025)
Business organizations today are exposed to many problems that are transmitted to them from other organizations operating in the same environment in which they operate. These organizations are able to continue to provide their work when they possess organizational immunity based on its dimensions (organizational learning, organizational genes, organizational memory), which requires Treatments with administrative tools to achieve this. Among these tools is creative behavior in its dimensions (authenticity, flexibility, fluency, sensitivity to problems). Therefore, the current study came to clarify the impact of creative behavior in enhancing organizational immunity in Al-Hadbaa Food Industries Limited Company in Nineveh Governorate. To reach the goal of this study, the questionnaire was relied upon as a tool for collecting data. Its questions were directed to Al-Hadbaa Company employees, who numbered (110) employees out of (132) workers. Through the statistical laboratory and the required statistical tools, a number of results were reached, the most important of which is the presence of Correlation and impact between innovative behavior and enhancing organizational immunity in Al-Hadbaa Company, in addition to presenting a number of proposals.